2016
DOI: 10.1038/srep36549
|View full text |Cite
|
Sign up to set email alerts
|

Cationic bactericidal peptide 1018 does not specifically target the stringent response alarmone (p)ppGpp

Abstract: The bacterial stringent response is a key regulator of bacterial virulence, biofilm formation and antibiotic tolerance, and is a promising target for the development of new antibacterial compounds. The intracellular nucleotide (p)ppGpp acts as a messenger orchestrating the stringent response. A synthetic peptide 1018 was recently proposed to specifically disrupt biofilms by inhibiting the stringent response via direct interaction with (p)ppGpp (de la Fuente-Núñez et al. (2014) PLoS Pathogens). We have interrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 48 publications
2
33
0
1
Order By: Relevance
“…Thus, to our knowledge, only the peptides 1018 and DJK-5 have been shown to provide a possible therapeutic approach against Gram-positive and Gram-negative pathogens in vertebrate infection models ( Achtman et al, 2012 ; Mansour et al, 2016 ). Recently, the observation that 1018 targets the cellular stress response had been challenged ( Andresen et al, 2016 ). However, the methodological procedures described by Andresen et al (2016) have serious issues including the use of microtiter plate adherence assays and crystal violet staining (which does not discriminate between live cells and bacterial debris) to assess biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to our knowledge, only the peptides 1018 and DJK-5 have been shown to provide a possible therapeutic approach against Gram-positive and Gram-negative pathogens in vertebrate infection models ( Achtman et al, 2012 ; Mansour et al, 2016 ). Recently, the observation that 1018 targets the cellular stress response had been challenged ( Andresen et al, 2016 ). However, the methodological procedures described by Andresen et al (2016) have serious issues including the use of microtiter plate adherence assays and crystal violet staining (which does not discriminate between live cells and bacterial debris) to assess biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the observation that 1018 targets the cellular stress response had been challenged ( Andresen et al, 2016 ). However, the methodological procedures described by Andresen et al (2016) have serious issues including the use of microtiter plate adherence assays and crystal violet staining (which does not discriminate between live cells and bacterial debris) to assess biofilm formation. Crystal violet experiments show large variations and are quite poor for accurately assessing anti-biofilm activity, especially when set up as a MIC experiment where peptides are added to planktonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules were suggested to act either via direct inhibition of RSHs, such as the (p)ppGpp analogue Relacin (21), or via catalytic hydrolysis of (p)ppGpp, such as antibiofilm peptide 1018 and its derivatives (22, 23). However, our follow-up studies have shown that neither Relacin nor peptide 1018 specifically inhibits the stringent response in live cells (24, 25). …”
Section: Introductionmentioning
confidence: 88%
“…In contrast, a dodecamer peptide termed 1018, by specifically marking (p)ppGpp for degradation, promotes dispersal of biofilm of a wide range of Gram‐positive and Gram‐negative species (de la Fuente‐Núñez et al ., ; Reffuveille et al ., ). However, these findings have been recently challenged by a study showing that the dispersal activity of peptide 1018 does not rely on the (p)ppGpp response, but rather on an unknown mechanism (Andresen et al ., ).…”
Section: Molecular Mechanisms Governing Biofilm Dispersalmentioning
confidence: 99%